Effectiveness and Safety of Acupuncture for the Treatment of Alzheimer's Disease: A Systematic Review and Meta-Analysis - Wang, Yun-Yun; Yu, Shao-Fu; Xue, Hong-Yang; Li, Yang; Zhao, Chen; Jin, Ying-Hui (Frontiers in Aging Neuroscience, 2020)
The effects of acupuncture on in Alzheimer' s Disease (AD) outcomes remain controversial. The aim of this review was to evaluate the effectiveness and safety of acupuncture for the treatment of AD. Results: Thirty trials involving 2045 patients were included. Acupuncture plus drug therapy may have been more beneficial for general cognitive function in AD patients than drug therapy alone (short-term treatment: MD = 1.94, 95% CI: 1.11, 2.77; p < 0.01; medium-term treatment: MD = 4.41, 95% CI: 1.83, 7.00; p < 0.01). People who received acupuncture plus drug therapy attained higher ADL scores than patients who received drug therapy alone for a medium-term treatment duration (MD = -2.14; 95% CI: -3.69, -0.59; p < 0.01). However, there is no statistically significant on subgroup effect when comparing acupuncture treatment with drug therapy, acupuncture plus drug therapy with drug therapy alone on MMSE and ADL(p > 0.05). There was also no significant difference on general cognitive function, ADL, incidence of adverse events between acupuncture treatment and drug therapy (p > 0.05).